A life course analysis of income and incident AMI - a Danish register based cohort study. (13th November 2019) - Lund, R; Kriegbaum, M; Andersen, I; Hougaard, C O; Brønnum-Hansen, H
Abstract: Background: Social inequality in ischemic heart disease has been related to socioeconomic position in childhood, early and late adulthood. However, the impact of relative level of accumulated income periods across adult life course and the potential gender and age differences has not been investigated. The aim was to investigate the association between relative level of accumulated income across the life course and Acute myocardial infarction (AMI) from age 60+ and to study if the associations differ by gender and exposure in different age groups (30-39 years, 40-49 years and 50-59 years). Methods: All Danes born 1935-54 N = 1, 235, 139 were followed-up in registers for incident AMI (ICD8: 410, ICD10: I20, I21) from age 60+, (42, 669 cases). The The Accumulated Proportional Deviation from Median Equivalized Income = APDMEI for each gender/age /calendar year strata was constructed and divided in quartiles. The analyses stratified by birth cohort included all Danes born in 1955-70 (alive and reached age 40) N = 1, 144, 264, 1945-64 (alive and reached age 50), N = 1, 434, 769, 1935-1954 (alive and reached age 60) N = 1, 235, 139 including outcomes in the following 10 year period. Cox's proportional hazard models adjusted for educational level, ethnic background and birth cohort. Results: Among men, those in the lowest APDMEI quartile had a HR 1.40 (1.35-1.45) of AMI compared to the highest quartile, second and third highest quartiles had HR of 1.24 (1.20-1.28) and 1.14 (1.10-1.18), respectively. Among women the lowest quartile had a HR of 1.78 (1.69-1.88), the second 1.45 (1.37-1.53) and the third 1.19 (1.13-1.26). The social gradient was similar across the different age-groups. Conclusions: The risk of AMI increased with lower levels of relative accumulated income across the life course. While men generally had a higher risk of AMI, the social gradient was steeper in women. There was no indication of a specific sensitive age period for exposure to relative level of accumulated income. Key messages: Accumulated low income is associated with higher AMI risk in both men and women, but with larger relative differences between high and low accumulated income in women. This study adds a new approach to the study of inequalities in AMI by integrating duration and extent of low income into a relative measure of accumulated income.